Sheep and goat farming and grasslands conservation: in need of proper policies - Hadjigeorgiou I. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Mediterranean landscapes have been formed through human activity for millennia, which resulted in a particularly rich and rare biodiversity. Among these activities grazing is the most beneficial on biodiversity. However, the sheep and goat sector is rapidly transforming into sedentary-housed types and pastoral land is abandoned. The Greek example is presented and a range of policies are suggested to halt this trend and conserve pastoral land biodiversity in Mediterranean.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)